Assessment of Afforestation Activities in Thrace Region using Some Oak (Quercus sp.) Varieties - Özel, Halil Barış; Tandoğan, Mesut; Şahi̇n, Nülüfer; Aslan, Vedat; Özdemi̇r, Mehmet; Şevi̇k, Hakan (Kastamonu University, 2023)
In this study, which is a preliminary assessment, afforestation studies established at different times with different oak species (Quercus sp.) in the Thrace Region were examined. Accordingly, as a result of the variance analysis applied to the data of the percentage of survival variable, which is important in terms of adaptation ability, it was determined that there was a statistically significant difference at the P˂0.05 confidence level in terms of afforestation areas. In this respect, as a result of Duncan test performed at P˂0.05 confidence level to create homogeneous groups, Ulukonak oak plantation area established with Q. infectoria with a survival rate of 89% is in the first group, and this group is classified with a survival percentage of 78%. Celaliye plantation area established with Q. cerris species followed. In the study, mean values were determined in terms of afforestation areas regarding the quantitative and morphological characters determined in the trial areas taken from the oak afforestation areas. When these data are examined, the mean diameter value varies between 2.3-5.1 cm in Q. petraea afforestation areas of different ages, 2.0-3.6 cm in Q. infectoria afforestation areas, 3.5 cm in Q. frainetto and Q. cerris. It was determined to be 4.9 cm in. Mean height value varies between 2.36-5.58m in Q. petraea afforestation areas, 2.30-2.98m in Q. infectoria afforestation areas, 3.62m in Q. frainetto and 3.93m in Q. cerris. has been found to be. The crown symmetry is generally asymmetrical in all afforestation areas, regardless of the oak species. Stem straightness, on the other hand, was in the curve category for all afforestation areas. As a result of the variance analysis applied to the average volume values determined in the sampling areas, a statistically significant difference was determined between the forestation areas at the P˂0.05 confidence level. In this context, afforestation area established with Q. petraea oak species formed the first group with an average volume value of 0.00930 m3, as a result of Duncan Range Test performed at P˂0.05 confidence level to create homogeneous groups in terms of afforestation areas.
Keywords: Plant Physiology; Bitki Fizyolojisi; Oak; Afforestation; Survial Percentage; Adaptation; Growth; 15. Life on land